Metal cutting - Trent, E. M. (Edward Moor) (Butterworth Heinemann, 1991)
Expanded and revised to include changes and additions to metal cutting theory. Covers developments in tool materials and industrial practice over the last seven years. Describes the stresses and temperatures acting on cutting tools and explains their influence on performance. Discusses tool wear which determines cutting efficiency. Details machinability and control of tool material structure and composition.